Zéro pesticide Un nouveau paradigme de recherche pour une agriculture durable - Jacquet, Florence; Jeuffroy, Marie-Hélène; Jouan, Julia; Le Cadre, Edith; Malausa, Thibaut; Reboud, Xavier; Huyghe, Christian (éditions Quae, 2022)
The use of chemical pesticides is a major societal concern because of their negative impacts on the environment and health. The Priority Research Programme (PPR) "Cultiver et Protéger Autrement" (Growing and Protecting Differently), led by INRAE, plays a structuring role in the evolution of scientific communities and in the emergence of scientific fronts allowing for pesticide-free crop protection. The aim of the book is to explain the foundations of this strategy and the principles of action. By setting itself a zero pesticide course, research is attempting to overcome the current obstacles and produce breakthrough innovations in the biotechnical and socio-economic fields. In addition to research, teaching and the agricultural sector, this book also targets innovation, development and advisory actors.